Perspectives of health workers on the facilitators and barriers to antiretroviral therapy adherence following intensive adherence counseling in Northern Uganda - Humphrey Beja; Daisy Nakayiwa; Innocent Ocitti Owachgiu; Micheal Tonny Edek; Veronic Kobusinge; Oscar Akaki; Samson Udho (Frontiers in Health Services)
BackgroundIn some contexts, people living with HIV (PLWH) who are virally non-suppressed and participating in an intensive adherence counseling (IAC) program have demonstrated non-adherence to antiretroviral therapy (ART) even after IAC. There is limited literature on the facilitators and barriers to ART adherence following IAC.ObjectiveThis study aimed to explore the perspectives of healthcare workers (HCWs) on the facilitators and barriers to ART adherence following IAC among PLWH in Northern Uganda.MethodsThis was a descriptive qualitative study conducted among HCWs at the ART clinics of the two highest-volume public health facilities in Lira District. We purposively sampled 15 study participants and conducted face-to-face in-depth interviews using an interview guide formulated based on the components of the Capability, Opportunity, and Motivation framework for Behavior change (COM-B framework). Thematic analysis was used based on the COM-B framework. In this study, the desired behavior was ART adherence following IAC. Factors that were perceived to positively affect any component of the COM-B framework were classified as facilitators and those that were perceived to negatively affect were classified as barriers.ResultsThe majority of the participants were females (53%), diploma holders (40%), and nurses (40%). The perceived facilitators and barriers to ART adherence following IAC emerged as six key themes under the subdivisions of the three domains of the COM-B framework: cognitive and emotional processes, physical and practical skills, accessibility and material resources, social relationships and cultural dynamics, cognitive beliefs and aspirations, and finally, emotional and subconscious drivers. These themes were identified as either facilitators or barriers to ART adherence following IAC depending on the lenses of interpretation.ConclusionsThis study offers a multidimensional insight into the facilitators and barriers to ART adherence following IAC and how the behavior influencing ART adherence can be optimized. The results suggest that optimizing cognitive and emotional processes, physical and practical skills, accessibility and material resources, social relationships and cultural dynamics, cognitive beliefs and aspirations, and emotional and subconscious drivers during IAC and any ART adherence-related intervention could yield the best level of ART adherence among the PLWH who are virally non-suppressed and on ART.